Penyuluhan Pendidikan Seks Usia Muda untuk Meningkatkan Pengetahuan dan Sikap Positif Siswa: Young Age Sex Education Counseling to Improve Knowledge and Positive Attitudes of Students at SMP - Sianturi, Marta Imelda Br; Hutasoit, Dessy Meilani; Togatorop, Linawati; Sihombing, Faija (Chakra Brahmanda Lentera Institute, 2026)
Young age sex education is often considered a taboo topic in Indonesian society, leading to a lack of understanding among adolescents. This can result in negative behaviors and risks such as sexual violence and unplanned pregnancy. This community service activity (PKM) aimed to provide accurate information and shape positive attitudes towards reproductive health among junior high school students. This service employed an educational, participatory, and applicative approach, consisting of three stages: preparation, implementation, and evaluation. The target participants were 30 students of class IX-6 at SMP Negeri 16 Medan, selected through purposive sampling. The intervention was conducted in two structured sessions using PowerPoint presentations, leaflets, and audiovisual media, covering the importance of sex education, reproductive organ function, ethics, norms, and how to avoid sexual deviations and violence. Evaluation was carried out using a pre-test and post-test knowledge questionnaire (10 items, KR-20=0.85) and observation. Data were analyzed using descriptive statistics and a Paired Sample T-Test. The activity successfully achieved its participant target. The results showed a significant increase in knowledge, with the average pre-test score of 5.2 (Sufficient category) rising to 8.1 (Good category) in the post-test (p-value=0.001). Observation also indicated a positive shift in participants' attitudes and understanding, as they were able to explain the importance of sex education and ways to avoid sexual violence. Counseling on sex education for young adolescents is effective in increasing knowledge and shaping positive attitudes towards reproductive health. Sustainable, school-based educational interventions are recommended as a routine part of adolescent health promotion programs.